NASA WorldWind: virtual globe for an open smart city - Brovelli,Maria A; Kilsedar,Candan E; Hogan,Patrick J; Prestifilippo,Gabriele; Zamboni,Giorgo (PeerJ Preprints, 2016)
In this paper, the open source framework NASA WorldWind is presented. NASA WorldWind comes with two versions. The Java version is well established in the market and has many customers. On the other side the new version, which is the Web version, Web WorldWind, is still at the dawn of development cycle, with many features implemented and already used in several applications, with a great future ahead. Moreover, some of the features available in the Web WorldWind are listed and a short comparison with Cesium library is provided. Additionally, an interesting application developed in the smart cities context with Web WorldWind is described.
Keywords: NASA WorldWind; Web; Free and Open Source Software; VIrtual Globes; Smart City; Sustainability; Data Collection